Mature tertiary lymphoid structures: important contributors to anti-tumor immune efficacy - Bao, Xinyu; Lin, Xuwen; Xie, Mei; Yao, Jie; Song, Jialin; Ma, Xidong; Zhang, Xin; Zhang, Yinguang; Liu, Yiming; Han, Wenya; Liang, Yiran; Hu, Hongling; et al. (Frontiers in Immunology, 2024)
Tertiary lymphoid structures (TLS) represents the ectopic aggregations of immune cells arising during chronic inflammation or tumor progression. In cancer, TLS are often associated with beneficial clinical outcomes in patients undergoing immunotherapy, underscoring their prognostic and predictive significance. Mature TLS, characterized by germinal centers and areas of T-cell and B-cell aggregation, are considered primary locations for activating and maintaining both humoral and cellular anti-tumor immune effects. Despite their recognized importance, the mechanisms driving the formation of mature TLS in cancer and their influence on the immune response within tumors remain insufficiently understood. Therefore, this review aims to comprehensively explore the structural composition, development mechanisms, maturity impact factors, immunological function, and innovative therapeutic strategies of mature TLS within the tumour microenvironment.The research summarized herein offers novel insights and considerations for therapeutic approaches to promote TLS generation and maturation in cancer patients,representing a promising avenue for future cancer therapies.